The history of complex problem solving - Fischer, Andreas; Greiff, Samuel; Funke, Joachim (The nature of problem solving, 2017)
Complex problem solving (CPS) is about reaching one’s goals taking into account a large number of highly interrelated aspects. CPS has a rich history in experimental and psychometric research. The chapter highlights some of the most important findings of this research and shows its relationship to interactive problem solving. More specifically, it 1) characterises typical human strategies and shortcomings in coping with complex problems; 2) summarises some of the most influential theories on cognitive aspects of CPS; and 3) outlines the history of including CPS skills and competency in assessment contexts. The last section summarises the current state of play and points out some trends for future research.